Innovation technology in the initial training of children by the example of sport games - Ruslana Sushko; Maryna Ibraimova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the characteristics of innovative technologies and the current state of organizational work with children at the initial stage of training in sports. Material and Methods: to understand the application of innovative technologies used coaches poll and summarized expert assessment specialists in the field of sports. Results: the current state of the question concerning the possibility of the initial training of children in early specialization in sports for example basketball, volleyball and tennis. Clarified the importance and necessity of innovative activities for children at the initial stage of training in sports. Conclusions: the identified innovative approaches for constructing the process of initial training in tennis, which are not observed in other kinds of sports.